2012
DOI: 10.1007/s11099-012-0035-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glomus mosseae on chlorophyll content, chlorophyll fluorescence parameters, and chloroplast ultrastructure of beach plum (Prunus maritima) under NaCl stress

Abstract: The present study was undertaken to investigate the effect of Glomus mosseae on chlorophyll (Chl) content, Chl fluorescence parameters and chloroplast ultrastructure of beach plum seedlings under 2% NaCl stress. The results showed that compared to control, both Chl a and Chl b contents of NaCl + G. mosseae treatment were significantly lower during the salt stress, while Chl a/b ratio increased significantly. The increase of minimal fluorescence of darkadapted state (F 0 ), and the decrease of maximal fluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 19 publications
4
28
0
Order By: Relevance
“…In the present study, the net photosynthetic rates of seedlings inoculated with F. mosseae 1 and F. mosseae 2 strains were significantly increased under salt stress conditions, which could be attributed to the ability of the AMF strains to enhance the photosynthetic pigment content, similar to that reported in previous studies [43,44]. The increased photosynthetic pigment content, which allows seedlings to obtain more energy from light [44], might be related to the increase in nutrient uptake caused by AMF [45], as indicated by the higher P and Mg contents in the seedlings inoculated with AMF. The net photosynthetic rates of Z. serrata seedlings inoculated with D. tortuosum strain were significantly higher under CK, but showed no difference under salt stress conditions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, the net photosynthetic rates of seedlings inoculated with F. mosseae 1 and F. mosseae 2 strains were significantly increased under salt stress conditions, which could be attributed to the ability of the AMF strains to enhance the photosynthetic pigment content, similar to that reported in previous studies [43,44]. The increased photosynthetic pigment content, which allows seedlings to obtain more energy from light [44], might be related to the increase in nutrient uptake caused by AMF [45], as indicated by the higher P and Mg contents in the seedlings inoculated with AMF. The net photosynthetic rates of Z. serrata seedlings inoculated with D. tortuosum strain were significantly higher under CK, but showed no difference under salt stress conditions.…”
Section: Discussionsupporting
confidence: 91%
“…Previous evidence has demonstrated that AMF can improve the photosynthetic ability of plants mainly by enhancing the gas exchange capacity, photosynthetic pigments content, and photochemistry and non-photochemistry of PSII and the water status of leaves [3,42]. In the present study, the net photosynthetic rates of seedlings inoculated with F. mosseae 1 and F. mosseae 2 strains were significantly increased under salt stress conditions, which could be attributed to the ability of the AMF strains to enhance the photosynthetic pigment content, similar to that reported in previous studies [43,44]. The increased photosynthetic pigment content, which allows seedlings to obtain more energy from light [44], might be related to the increase in nutrient uptake caused by AMF [45], as indicated by the higher P and Mg contents in the seedlings inoculated with AMF.…”
Section: Discussionsupporting
confidence: 91%
“…To tolerate high salinity, halophytes need to be capable of maintaining normal or even increased electron transfer efficiency, with the activities of enzymes for carbon fixation unaffected or even stimulated [33][34][35]. Reports in herbaceous salt-tolerant species showed that abundance of both light reaction proteins and Calvin cyclerelated enzymes, as well as both photosynthesis parameters and chlorophyll content were decreased under salt stress [30,[36][37][38][39]. Contrary to herbaceous species, our previous work found that photosynthetic activity in the woody plant K. candel was maintained under 400 mM salt stress by inducing the expression of proteins in the light-dependent reactions and Calvin cycle [25].…”
Section: Discussionmentioning
confidence: 99%
“…Chl content: Fresh mature leaves from the middle of apple trees were selected to evaluate the Chl content. Twenty leaf discs from fresh leaves were obtained using a punch (0.4 cm in diameter) and then incubated in 5 ml of 80% acetone in the dark for 24 h at 4°C (Zai et al 2012). After incubation, the extract was analyzed at 645 and 663 nm using a spectrophotometer (UV-2800, UNICO, China).…”
Section: Methodsmentioning
confidence: 99%
“…Chl fluorescence: To explore the variation of PSII activity, the parameters of Chl fluorescence of leaves was measured. The parameters F0, Fv/Fm, qp, and ΦPSII are a measure of the capacity of the primary photochemistry of PSII, and they are good indicators of the effect of environmental stress in photosynthesis (Baker and Rosenqvist 2004, Henriques 2009, Zai et al 2012. The F0 of leaves under shade were significantly higher than those exposed to full sunlight in the morning but were markedly lower in the afternoon.…”
Section: Gas Exchangementioning
confidence: 99%